Entrepreneurship Education in Nigeria: Challenges and Ways Forward - Saleh, Salihu; Yusuf, Audu; Ibrahim Musa Bwala; Mohammed Fori (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
The rapid increase in population growth of graduates in our schools had resulted into unemployment of tertiary institution graduates. This is because the government and private sector cannot have enough jobs to accommodate them. Consequently, entrepreneurship education was introduced in our tertiary institutions of learning to address this issue. Entrepreneurship education is the acquisition of skills, ability, competence which equip the recipients with initiative, creativity, risk taking ability, enthusiasm, independence, and vision for business venture. Graduates equip with knowledge and skills of entrepreneurship education would be aware of the existing businesses and think of it as alternative. Despite the advantages of the entrepreneurship education, it is faced with some challenges. These challenges among others are unavailable fund for teachings in practical terms for entrepreneurial education and start up and expansion of business ventures, inadequate facilities or equipments, and poor enabling environment for business. Finally, ways forward were suggested to address these challenges.